2015
DOI: 10.3390/atoms3030348
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-Assisted Generation of Sustainable Macroscopic Entanglement of Ultracold Gases

Abstract: Prospects for reaching persistent entanglement between two spatially-separated atomic Bose-Einstein condensates are outlined.The system setup comprises two condensates loaded in an optical lattice, which, in return, is confined within a high-Q optical resonator. The system is driven by an external laser that illuminates the atoms, such that photons can scatter into the cavity. In the superradiant phase, a cavity field is established, and we show that the emerging cavity-mediated interactions between the two co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…It is known that quantum fluctuation of both the matter wave field [58,59] and cavity light field [60] will induce a depletion of the BEC atoms. And, the scattered atoms can possess interesting properties such as correlation [61,62], entanglement [56] and squeezing [63] in the collision process. This would be a promising future researching direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that quantum fluctuation of both the matter wave field [58,59] and cavity light field [60] will induce a depletion of the BEC atoms. And, the scattered atoms can possess interesting properties such as correlation [61,62], entanglement [56] and squeezing [63] in the collision process. This would be a promising future researching direction.…”
Section: Discussionmentioning
confidence: 99%
“…via the cavity light field even though they are spatially separated, i.e., the cavity mediated interaction is a long range one [55][56][57].…”
Section: Medium Velocity Collisionmentioning
confidence: 99%
“…they consider the Tavis-Cummings model. Entanglement properties for the Dicke model has also been throughly explored [227,[803][804][805][806][807]. In Refs.…”
Section: The Dicke and Tavis-cummings Modelsmentioning
confidence: 99%
“…This is most easily seen by linearizing the original Dicke model in the Holstein-Primakoff boson representation [15,60]. In the superradiant phase, the resulting quadratic boson Hamiltonian contains additional squeezing terms, e.g.b 2 andâ 2 [62]. Within the effective linear model, the quantum fluctuations cause entanglement in the system, and for the closed Dicke model it has been found that the atom-field entanglement peaks at the critical point [63].…”
Section: Model B -Anisotropic Dicke Model (Normal Phase)mentioning
confidence: 99%